Forward Programming of Cardiac Stem Cells by Homogeneous Transduction with MYOCD plus TBX5. - Belian,E; Noseda,M; Abreu,Paiva MS; Leja,T; Sampson,R; Schneider,MD (PLOS One, 2015)
UNLABELLED: Adult cardiac stem cells (CSCs) express many endogenous cardiogenic transcription factors including members of the Gata, Hand, Mef2, and T-box family. Unlike its DNA-binding targets, Myocardin (Myocd)-a co-activator not only for serum response factor, but also for Gata4 and Tbx5-is not expressed in CSCs. We hypothesised that its absence was a limiting factor for reprogramming. Here, we sought to investigate the susceptibility of adult mouse Sca1+ side population CSCs to reprogramming by supplementing the triad of GATA4, MEF2C, and TBX5 (GMT), and more specifically by testing the effect of the missing co-activator, Myocd. Exogenous factors were expressed via doxycycline-inducible lentiviral vectors in various combinations. High throughput quantitative RT-PCR was used to test expression of 29 cardiac lineage markers two weeks post-induction. GMT induced more than half the analysed cardiac transcripts. However, no protein was detected for the induced sarcomeric genes Actc1, Myh6, and Myl2. Adding MYOCD to GMT affected only slightly the breadth and level of gene induction, but, importantly, triggered expression of all three proteins examined (α-cardiac actin, atrial natriuretic peptide, sarcomeric myosin heavy chains). MYOCD + TBX was the most effective pairwise combination in this system. In clonal derivatives homogenously expressing MYOCD + TBX at high levels, 93% of cardiac transcripts were up-regulated and all five proteins tested were visualized. IN SUMMARY: (1) GMT induced cardiac genes in CSCs, but not cardiac proteins under the conditions used. (2) Complementing GMT with MYOCD induced cardiac protein expression, indicating a more complete cardiac differentiation program. (3) Homogeneous transduction with MYOCD + TBX5 facilitated the identification of differentiating cells and the validation of this combinatorial reprogramming strategy. Together, these results highlight the pivotal importance of MYOCD in driving CSCs toward a cardiac muscle fate